Comprender mejor la Transferencia de Conocimientos en Salud y Seguridad en el Trabajo: Propuestas para una tipología de guías de prevención - Isabelle Faurie; Frédéric Planché; Serge Deltor; Camille Ricaud; Anaïs Grau; Céline Guy (Universidade do Porto, 2013)
The article is an original contribution to discussion on the role of Health and Safety and Working Conditions (HSWC) knowledge 'relays' and 'runners'. Using seven main indicators, it has been possible to class HSWC guides. Four categories have been identified: action, mediation, awareness and information guides. Based on this classification, analysis has shown that prevention guides can be recognised as practical tools (operational function), management tools (managerial function), communication tools (innovative function), or technical tools (regulatory function). The discussion specifies the benefit of this classification for defining prevention tools that are better adapted.